Produktivitas Varietas Padi Lahan Rawa Pasang Surut pada Berbagai Tipe Luapan Air Pasang - Niluh Putu Sri Ratmini; Hendra Hendra (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Ratmini NPS, Hendra H. 2019. Productivity of tidal swamp rice varieties in diferent types of flooding. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 559-566. Palembang: Unsri Press. Tidal swamp land is one of the agroecosystems that is the biggest contributor to food in South Sumatra. Increasing productivity of tidal land can be done by applying adaptive varieties. The development of varieties in tidal areas is very diverse. The purpose of this study is to determine the productivity level of several dominant varieties grown on tidal land in various types of flooding. Activities were carried out during the MH 2018/2019 Planting season in the form of interviews with farmer groups representing each type of overflow in Upang Karya village for A-type flooding and Mekar Mukt to represent B and C-Type flooding. Data collected included rice variety, cultivated area, fertilizer used and productivity. The collected data is tabulated and descriptive analysis is performed. The results showed that rice productivity in the same variety was higher in A-type flooding compared with B and C –type flooding . The highest productivity was obtained in Inpari 42 varieties with productivity of 7.4 t/ha and Inpari 32 with productivity 7.2 t/ha. Varieties that have high adaptability in A, B and C types flooding are Inpari 42 and 32.Keywords: productivity, tides, type of overflow, and varieties